Effects of human management on black carbon sorption/desorption during a water transfer project: Recognizing impacts and identifying mitigation possibilities. (15th May 2018) - Hao, Rong; Zhang, Jinliang; Wang, Peichao; Hu, Ronggui; Song, Yantun; Wu, Yupeng; Qiu, Guohong
Abstract: Water resources management is an important public concern. In this study, we examined the extent of sorption/desorption of trace pollutants to soil black carbon (BC) in the water level fluctuation zone (WLFZ) of the middle route of the South to North Water Transfer Project in China. In addition, we investigated the main management measures affecting these processes during the project. The results showed that the pseudo second-order model adequately describes the sorption/desorption of phenanthrene on the soil BC in the WLFZ. Water level fluctuation may indirectly influenced BC sorption/desorption by altering water chemistry. Water level residence time had negative effects on BC sorption in short-term experiments (days to months), but the impact gradually diminished with increased residence time. The results suggested that long-term field monitoring of water chemistry is urgent. During the initial period of water transfer, delaying the water supplies as drinking water source or directly irrigating crops could mitigate the adverse impacts. Future research should focus on the water-soluble products of BC degradation. The findings of this study should be useful in improving sustainable management of water resources for water transfer projects. Highlights: The pseudo second-order model adequately described BC sorption/desorption process. Water level fluctuation may indirectly influenced BC sorption/desorption. Water level residence time had short-term negative effects on BC sorption. Long-term field monitoring of water chemistry is essential. Delaying the water supply time could mitigate the adverse impacts.